R. G. Collingwood and the Presence of the Past. - Ahlskog, Jonas (Journal of the Philosophy of History, 2017)
This essay examines recent theories about the presence of the past from the perspective of Collingwood's philosophy of history. In the work of Eelco Runia and Frank Ankersmit among others, elaborate theories are offered for explaining how the past conditions and moves the present. Collingwood addresses the same kind of issues in his philosophy of history, but his ideas are very seldom discussed in presence theory. The aim of this essay is to place Collingwood's philosophy of history in dialogue with presence theory. I show that, even though Collingwood and presence theory have similar aims, Collingwood offers a fundamentally different account of how the past lives on in the here and now. Not only is Collingwood's account different - his conception of history undermines central presuppositions of presence theory. In conclusion, I argue that Collingwood's account shows how questions about the presence of the past are intimately connected with self-knowledge.